Overlapping exposure effects of pathogen and dimethoate on honeybee (Apis mellifera Linnaeus) metabolic rate and longevity - Pent, Kaarel; Naudi, Sigmar; Raimets, Risto; Jürison, Margret; Liiskmann, Egle; Karise, Reet (Frontiers in Physiology, 2023)
Declines in honeybee abundance have been observed worldwide during last decades. This is partly due to plant protection agents used in intensive farming, landscaping and infrastructure maintenance. Another type of factors negatively affecting honeybees is the spread of diseases caused by different pathogens and pests. Lately, more focus has been paid to the interactions between different overlapping stressors affecting honeybee health, the combination of these often being more detrimental compared to individual stressors. The most widely used stress-evaluating methods take into account lethal- or motorial changes of the individuals or colonies. Comparatively little honeybee research has examined changes in initial recovery potential and physiological symptoms of toxification. The aim of this study was to examine the combined effect of Nosema apis and N. ceranae (according to a newer classification Vairimorpha apis and V. ceranae), the common causes of nosemosis in the honeybee Apis mellifera L., with the insecticide dimethoate. In this study, honeybee mortality and metabolic rate were used to assess the combined effects interactions of Nosema ssp. and dimethoate. Our results showed that exposure to the low concentration of either dimethoate, either one or both species of Nosema ssp as single factors or in the combination had no significant effect on honeybee metabolic rate. The mortality increased with the two Nosema spp., as well as with infection by N. ceranae alone. The effect of dimethoate was observed only in combination with N. apis infection, which alone had no effect on individual honeybee mortality. This study demonstrates that the overlapping exposure to a non-lethal concentration of a pesticide and a pathogen can be hided by stronger stressor but become observable with milder stressors.